2019
DOI: 10.3390/su11236860
|View full text |Cite
|
Sign up to set email alerts
|

Silo-Busting: Overcoming the Greatest Threat to Organizational Performance

Abstract: Most organizations are set up to operate in some form of silos, such as vertical divisions or horizontal functions. At best, silos offer a practical way for organizations to operate efficiently. At worst, they create a silo mentality where departments do not want to exchange knowledge or information, hindering internal collaboration and organizational learning, thus preventing achievement of high performance and organizational sustainability. The silo mentality issue has been recognized for a long time as a re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
47
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 62 publications
(48 citation statements)
references
References 33 publications
0
47
0
1
Order By: Relevance
“…Whereas five studies stated their primary relevance [60,66,70,109,111], three discussed the role of environmental contingent events as a secondary matter [67,69,110]. Reward [60,70,109,111], evidence of benefit [69,110], and feedback [66,110] were the most prevalent types of consequences cited by these studies. Regarding the findings of mixed positive and negative outcomes from attempts of bridging silos, the role of behavioral consequences were not as strategic mediators to organizational change [65,71,72].…”
Section: Properties and Consequencesmentioning
confidence: 99%
See 4 more Smart Citations
“…Whereas five studies stated their primary relevance [60,66,70,109,111], three discussed the role of environmental contingent events as a secondary matter [67,69,110]. Reward [60,70,109,111], evidence of benefit [69,110], and feedback [66,110] were the most prevalent types of consequences cited by these studies. Regarding the findings of mixed positive and negative outcomes from attempts of bridging silos, the role of behavioral consequences were not as strategic mediators to organizational change [65,71,72].…”
Section: Properties and Consequencesmentioning
confidence: 99%
“…Some correlations were found between references to consequences, bridging effectivity, and outcomes from cross-silo collaboration. The eight studies that reported bridging silos with positive outcomes [60,66,67,69,70,[109][110][111] made reference to the use of consequences. Whereas five studies stated their primary relevance [60,66,70,109,111], three discussed the role of environmental contingent events as a secondary matter [67,69,110].…”
Section: Properties and Consequencesmentioning
confidence: 99%
See 3 more Smart Citations